Frataxin analysis using triple quadrupole mass spectrometry: application to a large heterogeneous clinical cohort - Lynch, David R.; Rojsajjakul, Teerapat; Subramony, S. H.; Perlman, Susan L.; Keita, Medina; Mesaros, Clementina; Blair, Ian A. (Journal of neurology, 2024)
Background Friedreich ataxia is a progressive multisystem disorder caused by deficiency of the protein frataxin; a small mitochondrial protein involved in iron sulfur cluster synthesis. Two types of frataxin exist: FXN-M, found in most cells, and FXN-E, found almost exclusively in red blood cells. Treatments in clinical trials include frataxin restoration by gene therapy, protein replacement, and epigenetic therapies, all of which necessitate sensitive assays for assessing frataxin levels. Methods In the present study, we have used a triple quadrupole mass spectrometry-based assay to examine the features of both types of frataxin levels in blood in a large heterogenous cohort of 106 patients with FRDA. Results Frataxin levels (FXN-E and FXN M) were predicted by GAA repeat length in regression models ( R 2 values = 0.51 and 0.27, respectively), and conversely frataxin levels predicted clinical status as determined by modified Friedreich Ataxia Rating scale scores and by disability status ( R 2 values = 0.13–0.16). There was no significant change in frataxin levels in individual subjects over time, and apart from start codon mutations, FXN-E and FXN-M levels were roughly equal. Accounting for hemoglobin levels in a smaller sub-cohort improved prediction of both FXN-E and FXN-M levels from R 2 values of (0.3–0.38 to 0.20–0.51). Conclusion The present data show that assay of FXN-M and FXN-E levels in blood provides an appropriate biofluid for assessing their repletion in particular clinical contexts.